2000
DOI: 10.1259/bjr.73.873.11064661
|View full text |Cite
|
Sign up to set email alerts
|

Extensive soft tissue uptake of 99Tcm methylene diphosphonate in a patient with multiple myeloma.

Abstract: Bone scintigraphy is not usually performed in multiple myeloma (MM), as marrow deposits characteristically show no tracer uptake. However, metastatic bone disease often mimics MM both clinically and biochemically, resulting in a substantial number of MM patients undergoing bone scintigraphy. Variable appearances in these cases have been reported, ranging from normal to a superscan, the latter a result of massive tracer uptake within bone. Soft tissue uptake has been documented, often when MM is complicated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Furthermore, extraosseous uptake on bone scan is observed in patients with renal failure as a result of a failure to excrete the radiopharmaceuticals through the kidneys [14]. Hypercalcemia and hyperparathyroidism resulting from chronic renal failure cause soft tissue microcalcification [14].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, extraosseous uptake on bone scan is observed in patients with renal failure as a result of a failure to excrete the radiopharmaceuticals through the kidneys [14]. Hypercalcemia and hyperparathyroidism resulting from chronic renal failure cause soft tissue microcalcification [14].…”
Section: Discussionmentioning
confidence: 99%
“…2 On bone scintigraphy, multiple myeloma with or without amyloidosis can present with varied skeletal uptakes (i.e., absent, normal, superscan). 7 The reason for this variation in the degree of bone tracer accumulation among multiple myeloma patients is not known. Evans et al reported a case of minimal skeletal uptake and marked bone tracer accumulation in the muscles on the bone scintigram in multiple myeloma and hypercalcemia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although they suggested an accumulation mechanism for muscular amyloid deposits and metastatic calcifi cations, they could not confi rm this hypothesis pathologically. 7 Kanoh et al reported that amyloid deposits, rather than metastatic calcifi cation, may affect bone tracer accumulation in soft tissues, 3 which suggests that amyloid deposits have a stronger affi nity for bone tracers than calcifi ed tissues, such as the skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Une atteinte érosive est rare, à type de géodes et/ou d'érosions souschondrales finement cernées d'ostéosclérose, correspondant à des dépôts focaux d'amylose [8] (Fig. 5 [2] peut montrer une fixation non spécifique des articulations atteintes, mais l'existence d'une fixation extrasquelettique du coeur ou de la moelle osseuse est évocatrice d'amylose [4,19].…”
Section: Synthèse Clinicobiologiqueunclassified